Anticipate, wait or don't invest? The strategic net present value approach to study expansion decisions under policy uncertainty. Issue 2 (5th December 2022) - Yanore, Lotte; Sok, Jaap; Oude Lansink, Alfons
Abstract: Dutch dairy farmers used different investment strategies in their production capacity in the periods around the abolishment of the European Union milk quota. Some farmers anticipated and expanded their production, others waited till expected policies were implemented or did not change their production. We develop a theoretical framework that integrates investment strategies—anticipating, waiting, or not investing—in the presence of policy uncertainty. We provide a numerical illustration of the framework to a typical Dutch dairy farm considering to expand the milk production. Results show that farmers would anticipate when they expect that the right system will be implemented with delay and will have low financial consequences. A low risk aversion reinforces the adoption of the anticipation strategy. The implications for policy and practice are discussed [EconLit Citatons: D22, Q00, Q18].